Biomechanical Comparison of Plantar-To-Dorsal and Dorsal-To-Plantar Screw Fixation Strength for Subtalar Arthrodesis. Issue 4 (16th October 2019) - Rodriguez, Ramon; Dun, Schouchen; He, Jun Kit; McKissack, Haley; Fleisig, Glenn S.; Jain, Mohit; Brahmbhatt, Ashish; Shah, Ashish
Category: Basic Sciences/Biologics, Hindfoot Introduction/Purpose: Arthrodesis of the subtalar joint is performed for various arthritic and instability problems to correct alignment and relieve pain. For talocalcaneal pathologies, isolated subtalar arthrodesis has been advocated with the advantages of lower risk of adjacent joint arthritis and nonunion of the transverse tarsal joint. Internal fixation techniques have varied over time and use of compression screws is common. The screws may be oriented from dorsal to plantar or plantar to dorsal. Arguments favoring one approach over another are based more on "expert opinion" than hard data. The goal of this study was to compare the biomechanical stability of these two constructs to evaluate which creates a more stable construct. Methods: Eight matched pairs of cadaver feet underwent subtalar joint arthrodesis with two 7.3-mm cannulated screws. Randomization was used to assign screw orientation, such that one foot in each pair was assigned dorsal to plantar screw orientation (DP group), and the other foot plantar to dorsal orientation (PD group). Standard surgical technique with fluoroscopy was used for each approach. Following fixation, each specimen was loaded to failure with a Bionix 858 MTS device, applying a downward axial force at a distance to create torque. Torque to failure was compared between DP and PD groups using Student's T-test, with p = 0.05 used to determine statistical significance. Results: The force to failure was 585.9 ± 201.1 N for the plantar-to-dorsal fixation and 667.2 ± 449.4 N for the dorsal-to-plantar fixation. The moment arm was 55.1 ± 4.7 mm for the dorsal-to-plantar fixation and 54.8 ± 3.9 mm for the plantar-to-dorsal fixation. Statistical analysis demonstrated that the mean torque to failure slightly favored the DP group (37.3 N-m) to the PD group (32.2 N-m). However, the difference between the two groups was not statistically significant (p = 0.55). Conclusion: There is no significant difference in strength between subtalar arthrodesis performed with dorsal-to-plantar screw orientation and plantar-to-dorsal screw orientation. This suggests that selection of technique should depend on the situation and the required advantages of each. Placing the screw from the heel up has the benefit of being an easier approach, allows access to tenser talar bone once the screw is through, and has less risk of neurovascular injury. The dorsal-to-plantar technique allows simple supine positioning of the patient, needs only two fluoroscopic views to check pin position, and allows the surgeon to manipulate the foot more easily.